ChemInform Abstract: [4 + 1] vs [4 + 2]: Catalytic Intramolecular Coupling Between Cyclobutanones and Trisubstituted Allenes via C—C Activation. Issue 15 (24th March 2016) - Zhou, Xuan; Dong, Guangbin
Abstract: The title reaction under either conditions A) or B), carried out with allenes containing an N‐Tos function, leads to formation of a [4.2.1]‐bicyclic nitrogen heterocycle with 2 quaternary carbon centers.